Assessment of bioelectrical phase angle as a predictor of nutritional status in patients with Crohn's disease: A cross sectional study. Issue 5 (May 2020) - Cioffi, Iolanda; Marra, Maurizio; Imperatore, Nicola; Pagano, Maria Carmen; Santarpia, Lidia; Alfonsi, Lucia; Testa, Anna; Sammarco, Rosa; Contaldo, Franco; Castiglione, Fabiana; Pasanisi, Fabrizio
Summary: Background & aims: The assessment of body composition (BC) can be used to identify malnutrition in patients with Crohn's disease (CD). The aim of this study was to evaluate the nutritional status of CD patients by assessing BC, phase angle (PhA) and muscle strength. Differences in disease duration and medications were also considered. Methods: Consecutive adult CD patients aged 18–65 years were enrolled in this cross-sectional study. Disease activity was clinically defined by the Crohn's Disease Activity Index (CDAI) in the active and quiescent phases. All participants underwent anthropometry, BC and handgrip-strength (HGS) measurements; additionally, blood samples were taken. Data from CD patients were also compared with age-, sex- and BMI-matched healthy people. Results: A total of 140 CD patients with a mean age of 38.8 ± 13.9 years and a mean body weight of 64.9 ± 12 kg were recruited and compared to controls. The findings showed that all nutritional parameters, especially PhA and HGS, were lower in CD patients than in controls, and these parameters were substantially impaired as disease activity increased. Active CD patients had a lower body weight and fat mass than both the quiescent and control groups. PhA was negatively correlated with age (r = −0.362; p = 0.000) and CDAI (r = −0.135; p = 0.001) but was positively associated with fat free mass (FFM) (r = 0.443; p = 0.000) and HGS (r = 0.539; p = 0.000). Similarly, serum protein markers were lower in the active CD group than in the quiescent group (p < 0.05). Disease duration and medications did not significantly affect nutritional status. Conclusions: BIA-derived PhA is a valid indicator of nutritional status in CD patients, and its values decreased with increasing disease activity. Additionally, small alterations in BC, such as low FFM, and reduced HGS values can be considered markers of nutritional deficiency. Therefore, the assessment of BC should be recommended in clinical practice for screening and monitoring the nutritional status of CD patients. Highlights: The assessment of body composition should be used for identifying malnutrition in patients with Crohn's Disease. Bioelectrical phase angle provides crucial information on cellular health and soft tissue hydration. Phase angle values decreased with increasing disease activity, resulting a valid indicator of nutritional status.